Organized crime as financial crime: the nature of organized crime as reflected in prosecutions and research - Albanese, Jay S. (The new technology of financial crime, 2023)
Organized crime is a financial crime because its objective is profit or other material gain. The provision of illicit goods and services dominates organized crime profit making. Sometimes an organized crime offense is directed at power or intimidation (in cases such as racketeering or extortion), but these actions are designed to ensure the survival and profitability of an ongoing criminal enterprise. Therefore, organized crime has important similarities to the white-collar forms of financial crimes. What has been lacking in organized crime research is a comparison of actual cases of organized crime (i.e., prosecutions and convictions) to determine the extent to which organized crime prosecutions correspond to the specific offenses being researched on organized crime. An entire calendar year of organized crime prosecutions and published research articles are examined to evaluate their similarities and differences. In addition, aspects of organized crime prosecutions reveal important similarities and differences from other forms of financial crime.